Pancreatic 18F-FDG uptake is increased in type 2 diabetes patients compared to non-diabetic controls - Bakker, Guido J.; Vanbellinghen, Manon C.; Scheithauer, Torsten P.; Verchere, C. Bruce; Stroes, Erik S.; Timmers, Nyanza K. L. M.; Herrema, Hilde; Nieuwdorp, Max; Verberne, Hein J.; van Raalte, Daniël H. (PloS one, 2019)
Increasing evidence indicates that the development of type 2 diabetes is driven by chronic low grade beta-cell inflammation. However, it is unclear whether pancreatic inflammation can be noninvasively visualized in type 2 diabetes patients. We aimed to assess pancreatic 18F-FDG uptake in type 2 diabetes patients and controls using 18F-fluorodeoxylglucose positron emission tomography/computed tomography (18F-FDG PET/CT). In this retrospective cross-sectional study, we enrolled 20 type 2 diabetes patients and 65 controls who had undergone a diagnostic 18F-FDG PET/CT scan and obtained standardized uptake values (SUVs) of pancreas and muscle. Pancreatic SUV was adjusted for background uptake in muscle and for fasting blood glucose concentrations. The maximum pancreatic SUVs adjusted for background muscle uptake (SUVmax.m) and fasting blood glucose concentration (SUVglucose) were significantly higher in diabetes patients compared to controls (median 2.86 [IQR 2.24-4.36] compared to 2.15 [IQR 1.51-2.83], p = 0.006 and median 2.76 [IQR 1.18-4.34] compared to 1.91 [IQR 1.27-2.55], p<0.001, respectively). In linear regression adjusting for age and body mass index, diabetes remained the main predictor of SUVmax.m and SUVglucose. Pancreatic 18F-FDG uptake adjusted for background muscle uptake and fasting blood glucose concentration was significantly increased in type 2 diabetes patients.